Hacia una nueva categorización de las unidades fraseológicas desde una perspectiva histórica: locuciones prepositivas y formas locucionales prepositivas en el castellano del siglo XIV - David Porcel Bueno (E-Spania)
The main aim of the historical phraseology is to study the origin and the grammatical functioning of the phraseological units throughout history, showing the discursive circumstances in which they appeared and their specific use. In this paper, we have carried out a diachronic analysis that allows us to define, classify and characterize the prepositional locutions and the prepositional locutional forms that are present in the medieval wisdom literature from the 14th century, a genre which is especially important in the development of the Spanish phraseology.